Construction of emergency dispatching and controlling platform for multi-elevator in cloud computing. Issue 4 (11th November 2021) - Liu, Junjun; Wu, Jian; Guo, Lanzhong
Traditional elevator emergency dispatching platforms are limited by their computing power, they cannot automatically collect knowledge and learning information, and they can easily fall into local optimisation problems. Therefore, in the context of cloud computing, a multi-elevator emergency dispatching control platform is constructed through fuzzy control technology. According to the fuzzy control input amount, the weighting coefficients of waiting time, driving time and the congestion degree of the cabinet are continuously updated to obtain the optimal weighting coefficient. The maximum membership degree method is used to perform the deblurring processing, and the maximum value in the fuzzy output vector is used as the data after the deblurring processing to obtain the emergency dispatching result of multiple elevators. The results show that the average waiting time of the platform is 20.35 s, less than other platform methods, which indicate that this platform has excellent dispatching performance and good application prospects.